Is 'Assisted Reproduction' Reproduction?. (19th June 2017) - Piotrowska, Monika
Abstract: With an increasing number of ways to 'assist' reproduction, some bioethicists have started to wonder what it takes to become a genetic parent. It is widely agreed that sharing genes is not enough to substantiate the parent–offspring relation, but what is? Without a better understanding of the concept of reproduction (and what it means to say that an organism has reproduced), our thinking about parent–offspring relations and the ethical issues surrounding them risk being unprincipled. Here, I address that problem by offering a principled account of reproduction—the Overlap, Development and Persistence account—which I believe best captures the meaning of 'genetic parenthood'.